2016
DOI: 10.1021/acs.bioconjchem.6b00002
|View full text |Cite
|
Sign up to set email alerts
|

Divalent Amino-Acid-Based Amphiphilic Antioxidants: Synthesis, Self-Assembling Properties, and Biological Evaluation

Abstract: We report herein the synthesis of a divalent amphiphilic carrier onto which α-phenyl-N-tert-butyl nitrone (PBN) and 6-hydroxy-2,5,7,8-tetramethylchroman-2-carboxylic acid (Trolox) antioxidants were grafted to give the divalent derivative called FATxPBN. The divalent carrier consists of two lysine amino acids as a scaffold upon which the antioxidant moieties are grafted, a perfluorinated chain that supplies hydrophobicity, and a sugar-based polar headgroup that ensures water solubility. For the sake of comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 45 publications
2
4
0
Order By: Relevance
“…TEM investigations using negatively stained samples of aqueous solutions of FATxPBN above the critical micellar concentration showed the formation of spherical micelles (Figure 5E,F) with a diameter range between ~6 and ~25 nm. In the TEM images, the micelles appear mostly ellipsoidal, and the average diameter determined by computer-assisted imaging analysis is ~16 ± 2 nm, which is in agreement with dynamic light scattering data [69]. However, TEM clearly demonstrated a large variety in shape and size of the formed micelles.…”
Section: (Cryo)tem Of Self-assembled Fluorinated Amphiphilessupporting
confidence: 78%
See 1 more Smart Citation
“…TEM investigations using negatively stained samples of aqueous solutions of FATxPBN above the critical micellar concentration showed the formation of spherical micelles (Figure 5E,F) with a diameter range between ~6 and ~25 nm. In the TEM images, the micelles appear mostly ellipsoidal, and the average diameter determined by computer-assisted imaging analysis is ~16 ± 2 nm, which is in agreement with dynamic light scattering data [69]. However, TEM clearly demonstrated a large variety in shape and size of the formed micelles.…”
Section: (Cryo)tem Of Self-assembled Fluorinated Amphiphilessupporting
confidence: 78%
“…Amphiphilicity is also a key feature for bioactivity and protection against in vitro and in vivo oxidative toxicity, for example, light-induced retinal degeneration [70]. Rosselin et al [69] synthesized the amphiphilic divalent antioxidant FATxPBN (Figure 5D) consisting of two lysine amino acids as a scaffold upon which two antioxidant moieties are grafted. An additional perfluorinated chain supplies additional hydrophobicity without inducing a cytolytic effect [71].…”
Section: (Cryo)tem Of Self-assembled Fluorinated Amphiphilesmentioning
confidence: 99%
“…30-40 µM). Trolox, FATxPBN, FATx and FAPBN present IC 50 (concentration required to half-reduce the oxidation in absence of antioxidant) values of 4.0, 0.6, 0.9, and 29.5 µM, respectively, no IC 50 was determined for PBN.The better lipid peroxidation inhibitor capacity of Trolox compare to PBN agrees with previous work, where we showed that Trolox was more efficient than PBN to scavenge ABTS +• radicals(22). All three fluorinated derivatives exhibit lower IC 50 than their parent derivatives.…”
supporting
confidence: 88%
“…In both cases, the authors demonstrated that compared to PBN, the derivatives presented an enhanced protective activity against stroke and retina light-induced damages, respectively. Along the same line, Trolox and PBN amphiphilic derivatives (21,22) have recently been synthesized. They are bearing, on one hand, a perfluorinated chain to increase hydrophobicity without inducing a cytolytic effect (23) and on the other hand, a sugar group to maintain water solubility ( Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation